Prescribing Outdoor Physical Activity to Children: Health Care Providers' Perspectives - Richard W. Christiana PhD; J. Joy James PhD; Rebecca A. Battista PhD (SAGE Publishing, 2017)
Little evidence exists on health care provider (HCP) prescriptions for children's outdoor physical activity (PA). Semistructured interviews were conducted with 15 children's HCPs to explore perspectives on outdoor PA prescription programs for children and barriers to implementation. Thematic analytic techniques were used to analyze the data. Most participants reported an awareness of health benefits to children being in the outdoors. Ten themes emerged from the data related to 3 thematic categories: (1) current strategies that HCPs are using to promote PA among children, (2) barriers that HCPs see to prescribing outdoor PA, and (3) potential strategies for promoting outdoor PA among children. Assessment of the local outdoor PA environment and resource development must be done prior to a prescription program. HCPs should be skilled in conducting conversations and setting goals related to outdoor PA tailored to the patient. Developing a system for follow-up with patients on established goals should also be included.